Aligning Qur’anic, hadith and shari'ah paradigms into the medical imaging practice = موائمة بين النماذج القرآنية والحديثية والشرعية في تطبيق التصوير الطبي - Zainuddin, Zainul Ibrahim (Department of Qurâ€™an and Sunnah Studies, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University, 2018)
Medical Imaging or Radiography practice has been dictated by the Western Worldview. Various professional guidelines are available to guide Medical Imaging professionals in terms of the professional and ethical aspects in the field. However, they are devoid of any references to the Divine Creator or spiritual associations. This effective secularisation of spiritual values and practices could result in distancing Muslim practitioners from the ideals that Islam champions. This paper examined selected professional guidelines identifying some of the common professional and ethical themes that they represent. Seven common themes or constructs were discussed alongside Qur’Énic verses (القرآنية الآيات), Hadith (الحديث) and the Maqasid and Qawa’id Al-Shar'iyyah (مقاصد وقواعد الشرعية). Aligning these paradigms to the professional expectations was done with the intention of reinforcing and enhancing further the spiritual mindedness and practice of the Muslim practitioners. It is hoped that the discussions could promote the formulation of the Code of Professional Practice for Muslim Medical Imaging Practitioners.